Reconstuction of Legal Protection Regulation for Service Customers of Payment System in Indonesia - Saryo, Saryo; Uwiyono, A.; Nurbaiti, Siti (UNES Law Review, 2023)
This dissertation conducted under the title “Reconstruction of Legal Protection Regulation for Service Customers of Payment System in Indonesia was based on the need for a strong legal basis concerning consumer protection of payment system since the existing legal regulation construction. In addition, its implementation is deemed in need of adjustment with the increasing development of product and service of the national payment system which is encouraged by the technological advancement that promote tons of innovation so it may increase the risk for the consumers. The present study was aimed at analyzing and describing three problems related to the construction of legal protection regulation for consumers of payment system services in Indonesia, the implementation of legal protection for the payment system service consumers, and the reconstruction of legal protection regulation for payment system service customers in Indonesia in the future. The theoretical basis employed was the theory of equality, legal certainty, and legal protection. The methodology used was normative with law approach, conceptual and comparison, and descriptive approach obtained from secondary data supported with the primary data which were analyzed qualitatively using deductive conclusion-making. The research result revealed that the construction of legal protection for customers of payment system services regulated in the Peraturan Bank Indonesia (PBI) Number 22/20/PBI/2020 concerning Legal Protection for Bank Indonesia Consumers was still considered low so it needed an adjustment. The implementation of consumer protection of payment system service including consumer complaint handling provided by the Payment Service Provider by Bank Indonesia was deemed in need of improvement or reconstruction in order to be able to give legal certainty to the customers. The reconstruction of PBI was conducted by adjusting and adding some articles including indemnity, personal data protection, establishment of an Alternative Payment System Dispute Resolution Institution, cyber risk, new product testing, and action mechanisms against unlicensed Payment Service Providers. The researcher in this study suggested the formation of new laws regulating the payment system in which consumer protection of the payment system should be regulated by referring to the comparison with other countries that have certain Laws concerning the payment system. The formation of laws will strengthen the legal basis in the activity of the national payment system as well as give legal certainty to the consumers and business practitioners in the payment system service.